RELATION ENVIRONMENTAL, CULTURAL / SOCIAL, AND HAZARDS OF DISSEMINATION OF AEDES AEGYPTI, VECTOR OF TRANSMISSION OF DENGUE AND POTENTIAL RISKS TO THE FEVER CHINKUNGUNYA, EPIDEMIOLOGICAL ANALYSIS OF THE CITY OF TAMBOARA-PR (Fiep Bulletin - online, 2016)
The growing epidemics of dengue in Brazil and in the state of Parana where the Northwest region showed a high incidence in the years 2013/2014 and the appearance of the first cases of fever Chinkungunya transmitted by the same vector, in northern Brazil warn measures preventive and scientific and epidemiological studies. The aim of this study is to evaluate cases of dengue in the northwest of the state of Paraná, and relate to environmental, cultural and social factors in a small city. The methodology used was through household survey which was used to search form prescribed by the Family Health Program and Endemic Disease Control of the municipality of Tamboara team-Pr, 1450 households were assessed representing 72.5% of the urban area, having identified outbreaks of probable breeding grounds for the vector of dengue and the risk of spread of the mosquito Aedes aegypti and albopictus, and geographic regions identified in three degrees of risk. We conclude from this study that environmental factors and the behavior of the population, associated with climatic factors in the northwestern region of Paraná state, contributed to the growing epidemics suffered, and that the work of vector control measures required in partnership of entities government managers, but mainly in the changing habits of the general population.
Keywords: Environmental Factors; Analysis; Epidemic